The Liability of Criminal Law for Perpetrators of Goods Embezzlement - Andri Winjaya Laksana; Akhmad Ikraam; Anila Robbani (Jurnal Justice Dialectical, 2024)
The crime of embezzlement has become one of the causes of violations of social rights and the erosion of social values in community life. However, is it already optimal in its law enforcement, especially in the criminal accountability that should be imposed on the perpetrators of embezzlement? This research aims first to understand the regulation of criminal liability for embezzlement offenders and second, to examine the challenges that constitute weaknesses in the criminal liability itself, which result in the persistence of such crimes, and the efforts to address them. This research method uses normative legal research. This research method uses legislative techniques related to the review of all relevant legal guidelines and policies. This approach is used to understand the regulations on criminal liability for perpetrators of embezzlement. In addition, this research also uses a conceptual and case-based approach. The results of this research are, first, that criminal liability for the perpetrator of embezzlement is based on three main elements: the defendant's ability to account for their actions, the presence of an element of fault, and the absence of exculpatory or justificatory reasons. These elements serve as a guide for judges in determining criminal sanctions. Second, in the enforcement of criminal accountability, there are three main hindering factors: the substance of the law, the structure of the law, and the facilities and infrastructure. To overcome these obstacles and minimize embezzlement crimes, efforts are needed through criminal law and preventive and repressive measures.